New phosphonate based corrosion inhibitors for mild steel in hydrochloric acid useful for industrial pickling processes: Experimental and theoretical approach - Gupta N.K.; Verma C.; Salghi R.; Lgaz H.; Mukherjee A.K.; Quraishi M.A. (My University, 2025)
The present work deals with the synthesis and study of the inhibition effect of three α-aminophosphonates, namely diethyl (((4-chlorophenyl)amino)(phenyl)methyl)phosphonate (APCI-1), diethyl (((4-chlorophenyl)amino)(4-methoxyphenyl)methyl)phosphonate (APCI-2) and diethyl (1-((4-chlorophenyl)amino)-3-phenylallyl)phosphonate (APCI-3), on mild steel corrosion in 1 M hydrochloric acid solution using both experimental and theoretical methods. Weight loss results showed that the inhibition performance of the studied compounds increases with the concentration and the maximum inhibition efficiency was obtained at just 564 × 10-6 M concentration. Among all the three tested inhibitors, APCI-3 showed the best result having an inhibition efficiency of 96.90%. The potentiodynamic polarization study indicates that these α-aminophosphonates act as mixed type inhibitors and predominantly function as a cathodic inhibitor. Adsorption of the tested APCIs on the metallic surface obeyed the El-Awady adsorption isotherm. The adsorption of these compounds on the metallic surface was also supported by the scanning electron microscopy (SEM) and atomic force microscopy (AFM) methods. A good insight about the inhibition mechanism of the tested compounds was derived using DFT based quantum chemical calculations for their neutral as well as protonated forms. The orientation of inhibitors on the metallic surface and the interaction energies of these molecules were obtained using molecular dynamic simulation studies. Both experimental and theoretical studies suggested that the inhibition efficiency of the tested compounds followed the order APCI-3 > APCI-2 > APCI-1 and well corroborated each other. © 2017 The Royal Society of Chemistry and the Centre National de la Recherche Scientifique.